479 The dynamics in leading cause of injury mortality by demographic traits in Ningbo, China: 2004–2013. (1st September 2016) - Li, Hui; Zhu, Yinchao; Xu, Guozhang; Wang, Yong; Chen, Jieping; Han, Liyuan
Abstract : Background: Injuries have emerged as a crucial public health concern in China, accounting for about 10% of total mortality. Methods: Data from the death registry system in Ningbo in the period 2004–2013 were analysed to explore the tendency of injuries, using linear regression model on a log and absolute scale of mortality rate respectively. Results: The average crude injury mortality rate was 56.37/100, 000/year, accounting for 9.09% of all deaths, and showed a substantial downturn (−73.28% of Annual Percent Change). The ratio of male to female was diminishing and the injury-related deaths were ageing significantly. MV traffic crashes, drowning and suicide had mainly contributed 50.87%, 18.18% and 10.52% for decrease of all-cause injury mortality rate respectively, instead, only fall had contributed 100% for increase. The greatest reduction occurred in rural-man, with the annual rate changes of −2.19/100, 000/year, followed by urban-man (−1.96/100, 000/year), urban-woman (−0.75/100, 000/year) and rural-woman (−0.58/100, 000/year) respectively. Alarmingly, women were disproportionately suffering from fall with a sharp increasing trend, especially in urban-woman. The average crude mortality in adults age 65 and older was 255.98/100, 000/year and displayed a increasing trend (β = 0.0143, p = 0.0299) . Conclusions: This study provides a comprehensive overview of the dynamic in injury-related mortality rate in a developed city in China, where some injury patterns are becoming similar with some high-income countries. Appropriate preventive strategies should be urgently initiated to control this aggressive evolution, basing on the successful experiences.